Work-related learning needs in university continuing education—A factor model based on Eraut’s workplace trajectories - Bianca Maria Tokarski; Andrea Ferretti; Mirjam Pfister; Eléonore Tran; Andrea Gurtner (Zeitschrift für Weiterbildungsforschung - Report, 2025)
Abstract University continuing education (UCE) operates at the intersection of academic standards and professional applicability, shaped by evolving workplace demands and the lifelong learning paradigm. This study focuses on students’ expectations for skill development and adaptability, employing Eraut’s workplace learning trajectories as a framework to assess and address these needs systematically. Based on this, a factor model of work-related learning needs in UCE is developed and evaluated. CFA and SEM analyses confirm the validity and reliability of a three-factor measurement model, with robust indicators significantly measuring the latent constructs and indicating alignment between the theoretical framework and empirical data.